Transcription-coupled and global genome repair in the Saccharomyces cerevisiae RPB2 gene at nucleotide resolution. - Tijsterman, M (1996)
Repair of UV-induced cyclobutane pyrimidine dimers (CPDs) was examined at single nucleotide resolution in the yeast Saccharomyces cerevisiae, using an improved protocol for genomic end-labelling. To obtain the sensitivity required for adduct detection in yeast, an oligonucleotide-directed enrichment step was introduced into the current methodology developed for adduct detection in Escherichia coli. With this method, heterogeneous repair of CPDs within the RPB2 locus is observed. Individual CPDs positioned in the transcribed strand are removed very efficiently with identical kinetics. This fast repair starts within 23 bases downstream of the transcription initiation site. The non-transcribed strand of the active gene exhibits slow repair without detectable repair variations between individual lesions. In contrast, CPDs positioned in the promoter region show profound repair heterogeneity. Here, CPDs at specific sites are removed very quickly, with comparable rates to CPDs positioned in the transcribed strand, while at other positions lesions are not repaired at all during the period studied. Interestingly, the fast repair in the promoter region is dependent on the RAD7 and RAD16 genes, as are the slowly repaired CPDs in this region and in the non-transcribed strand. This indicates that the global genome repair pathway is not intrinsically slow and at specific positions can be as efficient as the transcription-coupled repair pathway.